(untitled) (ModaPalavra e-periódico, 2013)
This research is a theoretical reflection, where we will seek a dialogue between authors that treat about communication theories like Herbert Marcuse and Jesús Martín-Barbero and about the relationship between fashion and communication, as Malcolm Barnard and Norval Baitello Jr. Our intent was to reflect on the communicational character of fashion systems and approach with our object of study of the future dissertation - the hip-hop fashion - theories of communication. This way allowed us to work at the end of the execution of a path that was beyond the common marketing approach when it comes to the relationship between communication and fashion systems, leading us to conclude that there is the possibility of carrying out further reflections and complex covering social dynamics and countercultural character of fashion systems.